Evaluation of Legal Products and Legal Advocacy in the Pekalongan City Regional Election: Strengthening Participatory and Transparent Local Democracy - Hamzani, Achmad Irwan; Hardiyanto, Fahrudin Eko (AKM, 2025)
This article is the result of community service in the Evaluation Working Meeting for the Preparation of Legal Products and Legal Advocacy for the 2024 Pekalongan City Pilkada held by the Pekalongan City General Election Commission (KPU). The author was a resource person in the activity. A working meeting was held with the aim of evaluating the effectiveness of regulations and legal advocacy strategies in strengthening the integrity and transparency of local election implementation. The KPU has prepared various legal products, including KPU Regulations, Decisions, Circulars, and Technical Guidelines, and disseminated them through the Legal Documentation and Information Network (JDIH). Legal advocacy is carried out by the Legal and Supervision Division of the Pekalongan City KPU in a preventive and responsive manner, by providing assistance and handling public complaints. The use of Information and Communication Technology (ICT) plays an important role in realizing the openness of information and increasing public participation through social media, websites, and digital applications. This evaluation involves multiple parties and produces strategic recommendations for improving the implementation of the next Pilkada. The synergy between adaptive legal products and inclusive ICT strategies is an important foundation for building accountable, participatory, and transparent local democracy.